Implementation plan for a new mineral policy development framework and mining cadastre system for Pakistan. Issue 2 (3rd June 2019) - Ashraf, Hamid; Cawood, Frederick
Abstract : Purpose: The purpose of this paper is to present an implementation plan for the new mineral policy development framework and mining cadastre system for Pakistan, which was developed in the first two papers of this series. Design/methodology/approach: This paper presents an implementation plan based on three fundamental building blocks, namely, implementing an enabling institutional framework and other key elements of mineral policy framework (building block 1); mineral database and mining cadastre system (building block 2); and monitoring and evaluation (building block 3). Findings: A new Ministry of Mineral Development (MMD) is suggested to be developed. A Mineral Development Advisory Committee (MDAC) is also suggested to be constituted under the Ministry of Planning and Development to oversee the development of the new MMD and to implement the actions suggested in the mineral policy development framework. The MDAC will implement the seven key elements of mineral policy development framework. Practical implications: The design schema of PakMining Cadastre System for secure mineral rights system to attract local and foreign investments is presented. The implementation of institutional reforms, constitution of Mining Cadastre Directorate and implementation of other policy development frameworks is suggested for enabling environment. A comprehensive account of implementation and monitoring strategy is devised to be followed initially by the advisory committee and then by the MMD. Originality/value: This paper presents original work on the implementation plan for a new mineral policy framework and mining cadastre system for Pakistan to extract maximum benefit from its mineral resources.